Precoder and Combiner Design for Generalized Spatial Modulation based Multiuser MIMO Systems - Brogueira, Bernardo; Pavia, Joao Pedro; Souto, Nuno; Correia, Americo (2020 23rd International Symposium on Wireless Personal Multimedia Communications (WPMC), 2020)
Multiple input multiple output (MIMO) schemes based on generalized spatial modulations (GSM) have been widely considered as potential candidate techniques for next-generation wireless networks, as they can improve both spectral and energy efficiency. In this paper we propose a multi-user MIMO system, where a base station transmits precoded GSM symbols to several receivers. In the adopted GSM approach, multiple antennas transmit different high-level QAM symbols simultaneously. The precoder is designed in order to remove interference between users while an iterative algorithm is applied at the receiver to accomplish single-user GSM detection. Simulation results show that the presented GSM MU-MIMO approach is capable to effectively exploit a large number of transmit antennas deployed at the transmitter and also provide performance gains over conventional MU-MIMO schemes with identical spectral efficiencies.